Postmortem Study of Meloxicam Toxicity in One Month Old Puppy - Chalise, S.; Singh, D.K. (NPI Journal of Science and Technology, 2024)
An intramuscular administration (2.5 mg per kg) of meloxicam caused anorexia, vomiting, and diarrhea within a few hours, followed by unconsciousness, anemia, severe dehydration, and death within 12 hours in a one-month-old puppy. Postmortem findings showed hepatomegaly and acute hemorrhagic inflammation of the abomasum, colon and kidneys. Histological examination revealed tubular hemorrhage and tissue necrosis, with widespread vascular damage in the kidneys. This study emphasized cautious dosing and monitoring of meloxicam in young puppies.